The First Case Report of Preschool-Onset SS/SLE Coexisting With NMOSD of Chinese Origin - Liu, Liqun; Tang, Li; Zhang, Lu; Li, Xingfang; Huang, Peng; Xiong, Jie; Xiao, Yangyang; Liu, Lingjuan (Frontiers in Immunology, 2022)
Systemic lupus erythematosus (SLE) is an autoimmune connective tissue disease (CTD), the main features are multiple serum autoantibodies and extensive involvement of multiple systems. The onset age of patients varies from child to middle-aged, nearly 1/5 in childhood. Sjogren's syndrome (SS) is also an autoimmune disease characterized by a high-degree lymphocytic infiltration of exocrine glands, usually occurring in middle-aged and older women, and rarely in childhood. Neuromyelitis Optica spectrum disorder (NMOSD) is an immune-mediated inflammatory demyelinating disease of the central nervous system (CNS) mainly involving the optic nerve and spinal cord. The coexistence of NMOSD and SLE and/or SS is well recognized by both neurologists and rheumatologists, but cases in children have been rarely reported. In this paper, we reported a case of a girl with onset at age 5 clinically featured by recurrent parotid gland enlargement, pancytopenia, hypocomplementemia, multiple positive serum antibodies and cirrhosis. She was initially diagnosed with SS/SLE overlap syndrome at 5-year-old. Four years later, the patient suffered a sudden vision loss and was examined to have positive AQP4 antibodies in serum and cerebrospinal fluid (CSF), and long segmental spinal swelling, in line with the diagnostic criteria for NMOSD. Up to now, the current patient is of the youngest onset age to develop SS/SLE coexisting with NMOSD, also with cirrhosis. Subsequently, we reviewed the literature and discussed the possible mechanisms of SS/SLE coexisting with NMOSD.